Everyday grand : soulful recipes for celebrating life's big and small moments - Adams, Jocelyn Delk; Massov, Olga (Clarkson Potter/Publishers, an imprint of Random House, 2023)
"Jocelyn Delk Adams believes every day deserves to be celebrated, from seemingly mundane weekdays to exuberant weekends and holidays. Her approachable take on comfort food features Southern-steeped recipes that are jazzed-up, remixed classics, all sprinkled with the vibrant, colorful personality she's best known for."--